2022
DOI: 10.3390/cryst12020290
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Aggregation of Lithium Salt in Spiro-OMeTAD for Perovskite Solar Cells

Abstract: High-efficiency and stable hole transport materials (HTMs) play an essential role in high-performance planar perovskite solar cells (PSCs). 2,2,7,7-tetrakis(N,N-di-p-methoxyphenylamine)-9,9-spirobi-fluorene (Spiro-OMeTAD) is often used as HTMs in perovskite solar cells because of its excellent characteristics, such as energy level matching with perovskite, good film-forming ability, and high solubility. However, the accumulation and hydrolysis of the common additive Li-TFSI in Spiro-OMeTAD can cause voids/pinh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The weakened role of plasticizer by using Zn­(TFSI) 2 and tBP can be assumed by the weight loss as a function of temperature in Figure . While the pristine spiro-MeOTAD exhibits a single step in weight loss (Figure a), spiro-MeOTAD with LiTFSI and tBP demonstrates discrete decay steps (Figure b), where the residual solvent, mainly composed of tBP, rapidly evaporates at the initial heating stage (<200 °C), whereas the initial weight loss is significantly inhibited with a gentle slope owing to the strong interaction of tBP in the presence of Zn­(TFSI) 2 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The weakened role of plasticizer by using Zn­(TFSI) 2 and tBP can be assumed by the weight loss as a function of temperature in Figure . While the pristine spiro-MeOTAD exhibits a single step in weight loss (Figure a), spiro-MeOTAD with LiTFSI and tBP demonstrates discrete decay steps (Figure b), where the residual solvent, mainly composed of tBP, rapidly evaporates at the initial heating stage (<200 °C), whereas the initial weight loss is significantly inhibited with a gentle slope owing to the strong interaction of tBP in the presence of Zn­(TFSI) 2 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…However, the pain point remains because of conductivity loss by the diffusion of lithium cation triggered by the presence of coadditive tBP and aggregation caused by evaporation of tBP. 35 Thus, an effective way together with the factors affecting the thermal stability of the Spiro-MeOTAD−based PSCs should be discovered to enhance the thermal stability of Spiro-MeOTAD. 36 In this work, the effects of the additives in the Spiro-MeOTAD film on the thermal stability of PSCs were systematically explored to unveil the origin of thermal instability of PSCs employing the additive-containing Spiro-MeOTAD film.…”
Section: Introductionmentioning
confidence: 99%
“…On the perspective of stability, the passivation benefits blocking the migration of ions from perovskite to Spiro-MeOTAD film and suppressing the diffusion of LiTFSI from Spiro-MeOTAD to perovskite, as well as controlling the underlying chemical reaction of tBP with perovskite surface. However, the pain point remains because of conductivity loss by the diffusion of lithium cation triggered by the presence of coadditive tBP and aggregation caused by evaporation of tBP . Thus, an effective way together with the factors affecting the thermal stability of the Spiro-MeOTAD–based PSCs should be discovered to enhance the thermal stability of Spiro-MeOTAD …”
Section: Introductionmentioning
confidence: 99%
“…More recently, Manish et al [13] reported an optimised PCE of 19.08% in FASnI 3 based solar cell device with TiO 2 as the ETL and spiro-OMeTAD as the HTL. Due to low hole mobility and conductivity in spiro-OMeTADs' pristine form [14], as well as self-aggregation when deposited as a thin film, the proposed structure was found to be inactive.…”
Section: Introductionmentioning
confidence: 99%